Authors (The Biblical archaeology review, 2025)
Mary R. Bachvarova (The Fall of Jerusalem: Who Was to Blame?) is a professor of Classics at Willamette University. She specializes in comparative religion and literature of the eastern Mediterranean. Alicia J. Batten (Ancient Courts and the Letter of James) is a professor of religious studies at the University of Waterloo. She specializes in the […]